2005
DOI: 10.1096/fj.04-3192com
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke metal‐catalyzed protein oxidation leads to vascular endothelial cell contraction by depolymerization of microtubules

Abstract: Smoking is a significant risk factor for development of atherosclerosis. However, the pathophysiology of smoking-mediated vessel wall damage is not understood. With tools ranging from analytical chemistry to cell biology, we show that cigarette smoke contains metals that catalyze the direct oxidation of cellular proteins by smoke oxidants. Oxidation of cellular proteins causes a loss of microtubule function, culminating in microtubule depolymerization and proteasome-dependent degradation of alpha-tubulin. As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 48 publications
7
92
0
2
Order By: Relevance
“…IL-6 has gained attention as the key cytokine in regulation of the immune response, which leads to a shift from Treg toward Th17 cells, 29 but because expression of IL-17 and the Treg marker FoxP3 did not significantly differ between rapamycinand vehicle-treated mice of group 2, we concluded that at this time point, IL-6 seems only to be an indicator for the endothelial cell damage, as has been shown before. 30,31 Nevertheless, further studies using cell-specific knockout mice, as has been shown by the group of Quaggin, 19,20 are needed to evaluate the influence of rapamycin on IL-6 and VEGF modulation in anti-GBM GN.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 has gained attention as the key cytokine in regulation of the immune response, which leads to a shift from Treg toward Th17 cells, 29 but because expression of IL-17 and the Treg marker FoxP3 did not significantly differ between rapamycinand vehicle-treated mice of group 2, we concluded that at this time point, IL-6 seems only to be an indicator for the endothelial cell damage, as has been shown before. 30,31 Nevertheless, further studies using cell-specific knockout mice, as has been shown by the group of Quaggin, 19,20 are needed to evaluate the influence of rapamycin on IL-6 and VEGF modulation in anti-GBM GN.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke chemicals were reported to lead to adhesion molecule expression on the surface of endothelial cells and induce the release of proatherogenic cytokines, such as interleukin-6 and interleukin-8. 57 These processes, in combination with cigarette smoke-induced increase in the number and activation of platelets, lead to a significant shift toward a prothrombotic and procoagulative state in the vascular wall of smokers. 38 The core of these processes is the activation of the NFkB cascade.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…61 Several experimental studies demonstrated that, apart from causing vascular endothelial dysfunction, cigarette smoke causes physical damage to the vascular endothelium (Figure). In essence, 2 forms of damage were observed: (1) contraction of endothelial cells, mediated by oxidation and collapse of the tubulin system, which is reversible and may be part of the clinical symptoms of smoking-caused reduction of FMD, 57 and (2) endothelial cell death. In general, all forms of cell death, that is, apoptosis, necrosis, programmed necrosis (necroptosis), and autophagy, were found to be induced by cigarette smoke chemicals.…”
Section: Arterioscler Thromb Vasc Biol March 2014mentioning
confidence: 99%
“…There are emerging data suggesting that the alteration of metal homeostasis in the human body by cigarette smoking plays a crucial role in the genesis of a number of diseases. We have recently shown that metals in cigarette smoke are essential in the process leading to damage of the vascular endothelium (1). Dysfunction and disruption of the vascular endothelium is the primary event in the genesis of atherosclerosis, which is the leading cause of death in developed countries and accounts for a dramatically increasing number of deaths in developing countries too.…”
Section: Introductionmentioning
confidence: 99%